(untitled) (International journal of artificial intelligence, 2026)
This article explores the spiritual and moral foundations of developing loyalty to the Motherland among pre-conscription military education students. The study emphasizes the role of patriotism, moral values, national identity, and civic responsibility in shaping students’ devotion to their country. It also highlights the importance of educational institutions, family, and social environment in strengthening patriotic consciousness and moral maturity. The article concludes that integrating spiritual and ethical education into military training contributes to the formation of disciplined, responsible, and socially active citizens.